Amnesia for Complex Naturalistic Scenes and for Objects Following Fornix Transection in the Rhesus Monkey. - Gaffan, D (1992)
Rhesus monkeys (Macaca mulatta) were trained to discriminate among many complex naturalistic scenes. The scenes were still frames from a cinema film. They were presented as the discriminative stimuli in a concurrent discrimination learning task in which each discriminative stimulus was presented on one trial each day. Learning of this task was severely impaired by fornix transection. The same animals were also deficient in a similar concurrent discrimination learning task, with each discriminative stimulus presented on one trial each day, but with objects, not complex scenes, as the stimulus material. The impairment in object discrimination learning in the present experiment is attributable to an interaction of object discrimination learning with scene discrimination learning, and can be understood as an effect of interference in long-term memory. In contrast to these impairments in long-term memory, a test of within-session learning of complex scenes, in which the average interval between successive presentations of the same stimulus was < 3 min, was performed without significant impairment by the fornix-transected animals. These results show that long-term memory for complex naturalistic scenes reveals analogues in the monkey of human episodic memory and its impairment in amnesia.